ANALISIS STRATEGI PEMBERDAYAAN INDUSTRI PERTAHANAN NASIONAL DALAM MENDUKUNG TERWUJUDNYA MINIMUM ESSENTIAL FORCE - Wardhana, Muhammad Andra; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
To deal with all potential threats originating from the development of the national, regional and global strategic environment, it is necessary to have a strategic target for national defense, namely the realization of the TNI's Minimum Essential Force (MEF). Indonesia, which is currently implementing a program to meet the minimum requirement for its military strength (MEF) and avoid dependence on producers and wants to reduce the spending budget of defense equipment manufacturers abroad, the Indonesian government has taken the initiative to empower domestic industry potentials to become producers of weapons. and the TNI war fleetThe SWOT method approach can be implemented by identifying various factors to formulate strategies. The analysis is based on logic that can maximize Strengths and Opportunities, but simultaneously minimize Weaknesses and Threats. The results of the SWOT analysis obtained 3 (three) priority strategies in implementing the empowerment of the National Defense Industry, namely increasing human resource capabilities, overcoming budget constraints and increasing technological capabilities by involving universities in conducting research on technology and implementing transfer of technology in every purchase of defense equipment from outside. A country that can all be implemented for the development of defense equipment independently.